Proceedings of the Third Technical Seminar on Marine Fishery Resources Survey in the South China Sea, Area III. Western Philippines. - SEAFDEC (Bangkok, Thailand Southeast Asian Fisheries Development Center, 2000)
Special Paper No. SEC/SP/41
Keywords: Marine fisheries; Fishery surveys; Fishery resources; Fishery oceanography